Psychological Context of Old Russian Iconography - O V Klypa (Peoples' Friendship University of Russia (RUDN University), 2013)
The psychological value of the Old Russian icons has not been fully apprehended up to now. The article considers the psychological concepts reflected in the Old Russian icons.